Associations between maternal reports of periconceptional fever from miscellaneous causes and structural birth defects. Issue 15 (6th August 2022) - Mohan Dass, Nithya Lakshmi; Botto, Lorenzo D.; Tinker, Sarah C.; Canfield, Mark A.; Finnell, Richard H.; Gallaway, Michael Shayne; Hashmi, Syed Shahrukh; Hoyt, Adrienne T.; Nembhard, Wendy N.; Waller, Dorothy K.; ,
Abstract: Background: Associations between birth defects and fevers attributed to colds, influenza, and urinary tract infections (UTIs) have been observed in previous studies. Our aim was to study associations between birth defects and fevers attributed to other causes. Methods: We analyzed data from 34, 862 participants in the National Birth Defects Prevention Study, a multistate case–control study of major structural birth defects. Using multivariable logistic regression, we assessed the association between maternal report of fever during early pregnancy due to causes other than colds, influenza, or UTI and 36 categories of birth defects. Results: Maternal reports of fever due to other causes were associated with significantly elevated odds ratios ranging from 1.93 to 10.60 for 8 of 36 birth defects, primarily involving the spine, limbs, and heart (spina bifida, intestinal atresia, intercalary limb deficiency, transverse limb deficiency, congenital heart defect with heterotaxy, tetralogy of Fallot, pulmonary atresia and atrial septal defect, not otherwise specified). Conclusion: Our data suggests fever itself or other physiologic changes associated with many infections are associated with some birth defects. Women who are pregnant or planning to become pregnant may want to consider speaking with their healthcare provider about the best ways to avoid infections that may cause fever and for guidance on how to treat fevers during pregnancy.